Modelo de gestión de inventario para optimizar los procesos productivos en la Empresa MAQGRO Cia. Ltda. - Rodríguez Gaón, Alexi Rodolfo (2020)
This research project was carried out with the aim of optimizing the production processes in the manufacture of maize Sheller (DGM-70 and DGM-100) in the company MAQGRO Cía. Ltda., which during its time of operation has presented deficiency in the inventories management of both raw material and finished product, this is mainly due to the lack of methods knowledge, techniques and tools that help to optimize inventory stocks, as well as other problems associated with the lack of communication between the involved areas. In principle. The Pareto diagram is used to determine the potential causes that cause the problem. Consequently, techniques and instruments such as direct observation and interviews to raise information on situ are applied, which is treated by the analytical method with which the results are obtained that will be discussed to have the conclusions and the main recommendations of implementing the proposed EOQ mathematical model that will allow the correct replenishment of materials in order to minimize the costs related to maintaining inventory and order form, so through the simulation, we will have better estimates with values close to the real ones where we will have a better stock control. The ABC inventory management system was carried out in which the most relevant items of both the inventory of finished product and raw material were determined, in addition, groups A, B, and C were broken down where group A is determined as the most relevant item, with the objective of having the company taking these products as a priority since they generate greater utility and benefits in the company's production processes, therefore taking importance in them will avoid problems such as stock breaks or excesses in the order of materials, loss of materials and also dissatisfaction with the needs of customers, thus generating profits as savings to the company Key words: Simulation, Optimize, MAQGRO Cía. Ltda., Inventory Management.